Analysis Of The Authority To Carry Out The Duties Of The Governor In The Implementation Of Local Government According To Regulations In Indonesia - Ahmad Ridwan; Rd. Yudi Anton Rikmadani (Eduvest - Journal of Universal Studies, 2022)
The purpose of this study is to 1) know and analyze the form of the governor's governing body (PLT) in managing the work of local governments. 2) Identify and analyze the legal implications of the governor's governing body (PLT) in managing the work of local governments. The research method used is a type of normative legal research. The results showed that 1) the regulation of the governor's implementing authority (PLT) in the operational management of local governments has not been so clear and firm. 74 Of 2016 is contrary to or contrary to norms/standards that are contrary to the letter from the head of BKN No. K.2630 / V.203 / 99. 2) The legal impact of the Governor's PLT on the implementation of local government work at the time of the Governor's PLT passed the Regional Regulation on APBD. Regulation of the Minister of Home Affairs No. 74 of 2016 concerning the Government and Deputy Governor, as well as the position of mayor and deputy mayor, is contrary to the notion of state sovereignty.